Mustafa al-Siba‘i and Islamic Socialism: Rejecting Western Ideologies and Promoting Social Solidarity - Abdillah, Faisal Ridho; Lutfi, Muhammad; Amru, Khobirul; Kamil, Ahmad Zaidanil (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2023)
In the twentieth century, Islam faced various ideological challenges, among them being socialism. There are claims that socialism is more consistent with Islamic values than other ideologies like capitalism. One prominent Muslim thinker of this group is Mustafa al-Siba‘i whose attempted to combine Islamic principles with those of socialism. This research examines his idea of Islamic socialism, his criticism of communism-Marxism, and the typology and contextualization of his thought. It uses a literary and historical approach, collecting data from al-Siba‘i’s works and historical analysis to achieve a more in-depth understanding of the main concepts in al-Siba‘i’s thought on Islamic socialism. The main concept of Islamic socialism is social solidarity, rooted in Islamic teachings and emphasizing the importance of social justice and shared prosperity. Al-Siba‘i criticized socialism-Marxism and capitalism as man-made and, therefore, imperfect systems that are fraught with fatal errors, while offering Islam as an alternative. He asserts that the principles of Islam based on the Qur’ān, hadith, and ijtihād provide a solid foundation for socialism in its original sense. As such, al-Siba‘i’s approach attempts to contextualize socialism within an Islamic framework, creating a unique view of how Islamic principles can be applied in the context of socialism.